Understanding The Influence Of Shadow Economy And Foreign Direct Investment On Corporate Tax Revenue In Latin America: The Moderating effect Of Corruption Control - Wiguna, Yordan; Wijaya, Suparna (Educoretax, 2024)
Taxation is an essential mechanism that funds government expenditures and underpins the growth and development of any country. This research examines the influence of the shadow economy and foreign direct investment (FDI) on corporate income tax revenue in Latin America, considering the moderating role of corruption control. Using panel data regression analysis, we analyze data from various Latin American countries to explore the complex interactions between these economic factors and tax revenue. Our findings indicate that corruption control has a positive and significant effect on corporate income tax revenue. However, the relationship between the shadow economy and tax revenue changes when moderated by corruption control. Without moderation, the shadow economy positively impacts tax revenue, but in the presence of higher corruption control, it leads to reduced tax revenue. Similarly, while FDI initially shows a positive impact on tax revenue, this effect turns negative when considering corruption control. These findings shed light on the nuanced relationships between economic factors and tax revenue in Latin America, offering valuable insights for policy formulation and future research.